AB0377 The knowledge and practice in vaccination of irish rheumatologists. (23rd January 2014) - McCarthy, E.M.; Azeez, M.; Fitzpatrick, F.; Donnelly, S.O.
Abstract : Background: Patients with inflammatory arthritis are at increased risk of infection. Despite increased attention to the topic of infection in the rheumatology literature, vaccination rates remain poor. Recently EULAR have published recommendations for vaccination in adult patients. The clinical practice of rheumatologists in adult practice is undocumented. Objectives: To establish the knowledge, attitudes and clinical practice of rheumatologists with respect to vaccination. Methods: All practicing Irish rheumatologists were surveyed. Basic knowledge, current clinical practice and opinions on interventions to improve vaccine uptake were established.Data collected was analysed using SPSS18. Results: Identification of live & inert vaccines: Knowledge of live and inert status of specific vaccinations is shown in Table 1 . A proportion incorrectly identified influenza, pneumococcal and hepatitis B vaccines as live.Herpes Zoster was incorrectly identified as inert by the majority. Knowledge of Safety, Efficacy and Scheduling of Vaccination: Knowledge of vaccination issues with respect to anti-TNF treatment was good with >90% aware live vaccinations are contraindicated in patients on anti-TNF therapy and ideally administered one month prior to commencing treatment. 94% knew that patients on anti-TNF therapy can achieve protection with pneumococcal and influenza vaccine.There was less certainty with respect to DMARD therapy with 37% (16/43) incorrectly agreeing that live vaccines were contraindicated in patients on DMARDs. Structured clinic practice: 57% (25/44) of those surveyed had no written departmental vaccination guidelines. 50% (n=22) of practicing rheumatologists do not enquire about vaccination history in clinic. Only 9% (n=4) record vaccination history in their clinic notes. The majority (52%) cited insufficient time with patients as the limiting factor. 82% (n=36) considered the development of vaccination guidelines specifically for rheumatology patients beneficial. Attitudes to Immunization & Service Improvement: A minority, 5% (n=2) considered the general rheumatology clinic the best setting in which to improve vaccination uptake. Rheumatologists favoured strategies to improve vaccination rates included a shared care option with the patients GP using a "vaccination passport" [48% (n=21)], while 45% (n=20) suggested the development of nurse specialist lead clinics Conclusions: Whilst their knowledge of vaccination issues was generally good rheumatologists practice with regards to vaccination is suboptimal. Most neither recommend nor record vaccination history in their clinic notes. Although a more proactive role needs to be taken by rheumatologists any strategy to improve vaccine uptake must be developed outside the clinic setting. The EULAR guidelines on vaccination should be used to formulate practices to improve vaccine compliance. Disclosure of Interest: None Declared